Hepatocyte Growth Factor-Loaded Biomaterials for Mesenchymal Stem Cell Recruitment - Julia van de Kamp; Willi Jahnen-Dechent; Bjoern Rath; Ruth Knuechel; Sabine Neuss (Hindawi Limited, 2013)
Human adult mesenchymal stem cells (MSC) can be readily harvested from bone marrow through aspiration. MSC are involved in tissue regeneration and repair, particularly in wound healing. Due to their high self-renewal capacity and excellent differentiation potential in vitro, MSC are ideally suited for regenerative medicine. The complex interactions of MSC with their environment and their influence on the molecular and functional levels are widely studied but not completely understood. MSC secrete, for example, hepatocyte growth factor (HGF), whose concentration is enhanced in wounded areas and which is shown to act as a chemoattractant for MSC. We produced HGF-loaded biomaterials based on collagen and fibrin gels to develop a recruitment system for endogenous MSC to improve wound healing. Here, we report that HGF incorporated into collagen or fibrin gels leads to enhanced and directed MSC migration in vitro. HGF-loaded biomaterials might be potentially used as in vivo wound dressings to recruit endogenous MSC from tissue-specific niches towards the wounded area. This novel approach may help to reduce costly multistep procedures of cell isolation, in vitro culture, and transplantation usually used in tissue engineering.